High‐Throughput NanoString Analysis of Oncogenic Human Papillomavirus and Tumor Microenvironment Transcription in Head and Neck Squamous Cell Carcinoma. Issue 5 (25th May 2021) - Stepp, Wesley H.
Abstract: Human papillomaviruses (HPVs), specifically high‐risk HPVs, are responsible for up to 3% of all cancers in women and up to 2% of all cancers in men. They have been identified as the etiological agent of cervical cancer and have been increasingly found to be the driver behind head and neck cancers of the oropharynx. A system in which we can simultaneously observe transcriptional changes to both a host's tumor microenvironment and its associated oncogenic driver (e.g., HPV) would be highly valuable for understanding HPV's role in tumorigenesis. This article describes a detailed methodology for utilizing high‐throughput RNA analysis to study viral transcription in formalin‐fixed, paraffin‐embedded clinical tumor samples. Although our lab utilizes these methods for the study of head and neck cancer, the principles contained within are widely applicable to all fields of HPV study. © 2021 Wiley Periodicals LLC. Basic Protocol : HPV16 transcript analysis using NanoString Support Protocol 1 : Preparation of RNA from formalin‐fixed, paraffin‐embedded slides Support Protocol 2 : Preparation of RNA from cell lysates Support Protocol 3 : Fluorometric RNA concentration and RNA integrity analysis Support Protocol 4 : Determination of input RNA based on DV300 calculation